2010
DOI: 10.1016/j.jneumeth.2010.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Chronux: A platform for analyzing neural signals

Abstract: Chronux is an open-source software package developed for the analysis of neural data. The current version of Chronux includes software for signal processing of neural time-series data including several specialized mini-packages for spike sorting, local regression, audio segmentation, and other data-analysis tasks typically encountered by a neuroscientist. Chronux is freely available along with user tutorials, sample data, and extensive documentation from http://chronux.org/.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
633
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 786 publications
(658 citation statements)
references
References 25 publications
0
633
0
Order By: Relevance
“…In the hippocampus, prominent oscillations have been noted at (5-10 Hz), slow ␥ (30 -50 Hz), fast ␥ (50 -90 Hz), , and ripple (130 -230 Hz) frequencies (Belluscio et al, 2012). Although numerous studies point to the role of synaptic and nonsynaptic coupling of neurons in the generation of oscillations, specific mechanisms that support the various rhythms are not well understood (Buzsáki and Draguhn, 2004;Klausberger and Somogyi, 2008;Isaacson and Scanziani, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the hippocampus, prominent oscillations have been noted at (5-10 Hz), slow ␥ (30 -50 Hz), fast ␥ (50 -90 Hz), , and ripple (130 -230 Hz) frequencies (Belluscio et al, 2012). Although numerous studies point to the role of synaptic and nonsynaptic coupling of neurons in the generation of oscillations, specific mechanisms that support the various rhythms are not well understood (Buzsáki and Draguhn, 2004;Klausberger and Somogyi, 2008;Isaacson and Scanziani, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Neurons can communicate with each other either synaptically, electrically through gap junctions, or both (Tamás et al, 1998;Galarreta and Hestrin, 1999;Fukuda and Kosaka, 2000;Thomson et al, 2002). Electrical coupling has been observed chiefly among neurons of the same interneuron class (Galarreta and Hestrin, 1999;Tamás et al, 2000;Deans et al, 2001;Szabadics et al, 2001;Beierlein et al, 2003;Blatow et al, 2003;Galarreta et al, 2004;Mancilla et al, 2007;Fanselow et al, 2008) and has been postulated to promote fast spike synchronization (Traub et al, 2001;Gibson et al, 2005;Hughes and Crunelli, 2007;Mancilla et al, 2007). A recent in vitro study, however, suggested that millisecond synchrony between inhibitory interneurons can be equally well achieved by chemical synapses (Hu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The frequency bands of low gamma, high gamma, and SWR were defined as 30-45, 60-90, and 150-250 Hz, respectively. For the first step of processing of LFP, we eliminated the direct current offset and slow fluctuations using MATLAB (MathWorks, Natick, MA), and the locdetrend function in Chronux 2.00 toolbox (Bokil et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…3SD for at least 15 ms. For the purpose of analyzing SWR associated with eating, we eliminated the data points for which the running speed was over 4 cm/s. We calculated SWR-triggered spectrograms using MATLAB (MathWorks, Natick, MA) and Chronux toolbox 2.00 (Bokil et al 2010). The window had a width of 100-ms and moved with 10-ms steps.…”
Section: Discussionmentioning
confidence: 99%
“…Data were analysed using custom code written in MATLAB (Mathworks Inc.) and CHRONUX [19]. Both animals were trained on a standard memory-guided saccade task and the foraging search task (figure 1).…”
Section: (B) Electrophysiological Recordingmentioning
confidence: 99%